Clinical severity and molecular characteristics of circulating and emerging rotaviruses in young children attending hospital emergency departments in France. (August 2016) - de Rougemont, A.; Kaplon, J.; Fremy, C.; Legrand-Guillien, M.-C.; Minoui-Tran, A.; Payan, C.; Vabret, A.; Mendes-Martins, L.; Chouchane, M.; Maudinas, R.; Huet, F.; Dubos, F.; et al.
Abstract: Group A rotavirus (RVA) is the leading cause of acute gastroenteritis in young children worldwide. A prospective surveillance network has been set up to investigate the virological and clinical features of RVA infections and to detect the emergence of potentially epidemic strains in France. From 2009 to 2014, RVA-positive stool samples were collected from 4800 children <5 years old attending the paediatric emergency units of 16 large hospitals. Rotaviruses were then genotyped by RT-PCR with regard to their outer capsid proteins VP4 and VP7. Genotyping of 4708 RVA showed that G1P[8] strains (62.2%) were predominant. The incidence of G9P[8] (11.5%), G3P[8] (10.4%) and G2P[4] (6.6%) strains varied considerably, whereas G4P[8] (2.7%) strains were circulating mostly locally. Of note, G12P[8] (1.6%) strains emerged during the seasons 2011–12 and 2012–13 with 4.1% and 3.0% prevalence, respectively. Overall, 40 possible zoonotic reassortants, such as G6 (33.3%) and G8 (15.4%) strains, were detected, and were mostly associated with P[6] (67.5%). Analysis of clinical records of 624 hospitalized children and severity scores from 282 of them showed no difference in clinical manifestations or severity in relation to the genotype. The relative stability of RVA genotypes currently co-circulating and the large predominance of P[8] type strains may ensure vaccine effectiveness in France. The surveillance will continue to monitor the emergence of new reassortants that might not respond to current vaccines, all the more so as all genotypes can cause severe infections in infants.